2011
DOI: 10.1124/jpet.111.183400
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble Guanylate Cyclase Stimulator BAY 41-2272 Inhibits Vascular Smooth Muscle Growth through the cAMP-Dependent Protein Kinase and cGMP-Dependent Protein Kinase Pathways

Abstract: Vascular smooth muscle (VSM) proliferation and migration are key components in vessel remodeling. Cyclic nucleotide signaling is protective and has long-served as a therapeutic target against undesired VSM growth. The present work analyzed the effects of the soluble guanylate cyclase (sGC) stimulator 3-(4-amino-5-cyclopropylpyrimidine-2-yl)-1-(2-fluorobenzyl)-1H-pyrazolo [3,4-b]pyridine [BAY 41-2272 (BAY)] on VSM growth, and we hypothesize that BAY has the capacity to reduce proliferation and migration via cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(106 citation statements)
references
References 35 publications
9
96
0
1
Order By: Relevance
“…Previously, we demonstrated in both rat commercial (A7R5) VSMCs and rat primary VSMCs that BAY increases cyclic nucleotides and inhibits vascular growth through processes involving VASP phosphorylation (Joshi et al, 2011;Mendelev et al, 2009). In this report we demonstrate for the first time that BAY increases the activity of protein kinases and that this system has the ability to regulate growth of VSMCs.…”
Section: Wwwintechopencommentioning
confidence: 64%
See 4 more Smart Citations
“…Previously, we demonstrated in both rat commercial (A7R5) VSMCs and rat primary VSMCs that BAY increases cyclic nucleotides and inhibits vascular growth through processes involving VASP phosphorylation (Joshi et al, 2011;Mendelev et al, 2009). In this report we demonstrate for the first time that BAY increases the activity of protein kinases and that this system has the ability to regulate growth of VSMCs.…”
Section: Wwwintechopencommentioning
confidence: 64%
“…We recently demonstrated that BAY, a potent stimulator of sGC, increased phosphorylation of VASP in a site-specific fashion in rat A7R5 VSMCs and in rat primary VSMCs (Joshi et al, 2011). In the current study we sought to identify kinases responsible for this selective phosphorylation of VASP induced by BAY.…”
Section: The Effect Of Kinase Inhibitors On Bay-induced Vasp Phosphormentioning
confidence: 99%
See 3 more Smart Citations